Application of biomaterials for glioblastoma treatment: Promises, advances, and challenges. (December 2022) - Abdul-Al, Mohamed; Saeinasab, Morvarid; Zare, Adriana; Barati, Masoumeh; Shakeri, Shahryar; Keykhosravi, Ehsan; Momeni-Moghaddam, Madjid; Najafzadeh, Mojgan; Keshel, Saeed Heidari; Farzi, Gholamali; Sefat, Farshid
Abstract: Angiogenesis and tumour cell proliferation characterise Glioblastoma Multiforme (GBM/GB), generally known as glioblastoma. The most dangerous type of glioma is GB, rapidly developing and frequently spreading across the brain parenchyma. This lethal brain cancer most commonly arises in the cerebral hemispheres of the frontal and temporal lobes of the brain and has the capacity to significantly penetrate surrounding tissue, making maximum surgical resection impossible owing to a high level of vascularisation. Because there are no transferrable characteristics that predispose to GB improvement, all identified hereditary mutations are somatic and acquired deviations. Current brain tumour therapy is hampered by inadequate medication transport through the BBB (Blood Brain Barrier) to the tumour bed. By altering preoperative and intraoperative tumour detection, biomaterials have considerably improved existing ability to investigate, diagnose, and treat brain tumours. Nanostructured polymer particles can transport drugs straight to the tumour bed for extended periods of time. Biomaterials can also be used to provide innovative medicines such as gene therapy, photodynamic therapy, anti-angiogenic therapy, and thermotherapy. The aim of this article is to provide an exhaustive assessment of the biomaterials and tissue engineering methods that have previously been employed to treat or diagnose glioblastoma.